Clinical Outcomes and Microbiological Characteristics of Sequence Type 11 Klebsiella pneumoniae Infection - Yang, Ping; Wu, Zhenchao; Liu, Chao; Zheng, Jiajia; Wu, Nan; Wu, Zhangli; Yi, Juan; Lu, Ming; Shen, Ning (Frontiers in Medicine, 2022)
Background Sequence type 11 (ST11) Klebsiella pneumoniae (Kp) is highly prevalent in China and is a typical sequence type among KPC-producing isolates. This study aimed to evaluate the clinical outcomes and microbiological features of ST11 Kp infections. Methods A retrospective cohort study was conducted at Peking University Third Hospital from January 2017 to March 2021. Clinical data were collected from medical records. Antimicrobial susceptibility testing and string tests were performed. Whole-genome sequencing was used to analyze the capsular serotypes, detect virulence-associated genes, and perform multilocus sequence typing. The risk of all-cause mortality in ST11 Kp-infected patients was compared to that in non-ST11 Kp-infected patients. Results From 139 patients infected with Kp, 49 ST11 Kp (35.3%) strains were isolated. The Charlson comorbidity index in the ST11 group was higher than that in the non-ST11 group (3.94 ± 1.59 vs. 2.41 ± 1.54, P = 0.001). A greater number of ST11 Kp-infected patients required ICU admission (46.9 vs. 16.7%, P < 0.001) and mechanical ventilation (28.6 vs. 10.0%, P = 0.005). All ST11 isolates presented a multidrug-resistant (MDR) phenotype, and twenty-nine (59.2%) hypervirulent Kp (hvKp) were identified. Twenty-four ST11 strains presented with hypermucoviscosity. The presence of capsular types K47 and K64 was frequent in the ST11 Kp strains (P < 0.001). The key virulence-associated genes rmpA, rmpA2, iucA, iroB, and peg344 were present in 26.5, 42.9, 59.2, 0, and 26.5% of the isolates, respectively, in the ST11 group. Twenty-one ST11 isolates harbored the combination of iucA+rmpA2. The 30-day mortality rate and sequential organ failure assessment (SOFA) score were significantly higher in ST11 Kp-infected patients than in non-ST11 Kp-infected patients (P < 0.01). ST11 Kp infection appeared to be an independent risk factor for mortality in ST11 Kp-infected patients. Conclusions A high prevalence of the ST11 clone was found in the hospital, which accounted for elevated antimicrobial resistance and exhibited great molecularly inferred virulence. Patients with ST11 Kp infection had a tendency toward increased 30-day mortality and SOFA scores. ST11 Kp infection was an independent risk factor for mortality, suggesting that enhanced surveillance and management are essential.